Integrasi Nilai Moderasi Beragama pada Pengelolaan Program Kearifan Lokal di Sekolah Budaya Jember - Hidayat, Rofiq (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Character education based on local wisdom is becoming increasingly important in the context of multicultural societies. This article explores the integration of interfaith moderation values within local wisdom programs in cultural schools, focusing on efforts to create a harmonious and tolerant learning environment. The study was conducted at SMPN 2 Jember, recognized as a cultural school, using a qualitative approach that involved data collection through observations, interviews, and document studies. The findings indicate that the integration of interfaith moderation values into the local wisdom curriculum not only enhances students' awareness of the importance of tolerance but also strengthens local cultural identity. The program encompasses various activities, such as batik vest creation, culturally friendly canteens, and regional language days, which serve as media for instilling interfaith moderation values. These findings are expected to contribute to the development of a more values-based educational model and serve as a reference for other schools in implementing local wisdom as part of character education.